2014
DOI: 10.1007/s40618-014-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Irisin in idiopathic foetal growth restriction

Abstract: The data suggest that umbilical artery irisin levels were lower in pregnancies complicated by foetal growth restriction. Such lower irisin levels may contribute to the pathogenesis of this common condition, and metabolic syndrome may be a long-term consequence of idiopathic FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
4
6
0
1
Order By: Relevance
“…In accordance with previous reports, we found that irisin concentrations were lower in newborns compared with their mothers [29, 30]; however, this difference was not present in mother–newborn pairs who did not go through labor (Fig 1A). In this regard, has been established that irisin secretion is increased by exercise [1, 3]; therefore, the physical stress related to labor [31], possibly mimicking physical activity, might explain the higher irisin levels in those newborns.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous reports, we found that irisin concentrations were lower in newborns compared with their mothers [29, 30]; however, this difference was not present in mother–newborn pairs who did not go through labor (Fig 1A). In this regard, has been established that irisin secretion is increased by exercise [1, 3]; therefore, the physical stress related to labor [31], possibly mimicking physical activity, might explain the higher irisin levels in those newborns.…”
Section: Discussionsupporting
confidence: 93%
“…We also found no correlation between umbilical artery irisin and gestational age, which is similar to the results of Ebert el al. [29, 38]. Under normal conditions, arterial cord blood protein concentration may be around 28–53% lower than the concentration in maternal serum [40], which is similar to what was found in the current study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, irisin deficiency in the IUGR fetus may be one of the missing links in the potential molecular pathways, responsible for the increased postnatal susceptibility of IUGR individuals to insulin resistance, obesity and obesity-related metabolic disorders. In accordance, a recent study documented lower umbilical artery irisin levels in pregnancies complicated by as stated "idiopathic (with no apparent cause) IUGR" [33].…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…A recent small study of irisin levels in umbilical cord arterial blood revealed positive correlation between irisin and fetal weight, and a statistically significant lower levels of irisin in growth restricted infants [18]. The authors did not find a difference between cord blood venous levels and maternal blood levels of irisin in the same study population.…”
Section: Resultsmentioning
confidence: 80%